Mortality prior to, during and after opioid maintenance treatment (OMT): A national prospective cross-registry study - Clausen, Thomas; Anchersen, Katinka; Waal, Helge (Drug and alcohol dependence, 2008)
Opioid maintenance treatment (OMT) is generally considered to reduce mortality in opiate dependents. However, the level of mortality reduction is still uncertain. This study investigates mortality reductions in an “intention-to-treat” perspective including all dropouts. The mortality reducing effects of OMT are examined both within treatment and post-treatment. The study separates overdose and total mortality reductions. The study is a prospective cross-registry study with up to 7 years follow-up. All opiate dependents in Norway who applied for OMT (a total of 3789 subjects) were cross-linked with data from the death registry from Statistics Norway. Date and cause of death were crossed with dates for initiation and termination of OMT, and subjects’ age and gender. A baseline was established from the waiting list mortality rate. Intention-to-treat was investigated by analysing mortality among the entire population that started OMT. Mortality in treatment was reduced to RR 0.5 (relative risk) compared with pre-treatment. In the “intention-to-treat” perspective, the mortality risk was reduced to RR 0.6 compared with pre-treatment. The patients who left the treatment programme showed a high-mortality rate, particularly males. OMT significantly reduces risk of mortality also when examined in an intention-to-treat perspective. Studies that evaluate effects of OMT only in patients retained in treatment tend to overestimate benefits. Levels of overdose mortality will influence the risk reduction. Cross-registry studies as the current one are an important supplement to other observational designs in this field.